The Pharmacological Effects of Fagonia cretica linn Ethanolic Extract on Isolated Rabbit Intestine - Ahmed, Aimun AE.; Elfeil, Mawahib E. H.; Ahmed, Samrin K. N.; Elsammani, Tasnim O. (International Journal of Pharmacology and Toxicology, 2013)
The aim of this study was to verify the pharmacological effect(s) of the Fagonia cretica linn (Zygophyllaceae) ethanolic extract and to determine the mechanism(s) underlay its action using isolated rabbit intestine. The cumulative dose-response curves of the Fagonia cretica extract and standard adrenaline were constructed using different doses ranged (10-3 - 102 µg/ml), and (10-9 - 10-5 M) alone, and  in the presence of a single dose of a blocker, then the values of EC50, Emax and pA2 were determined as mean ± S.E.M, and compared statistically. The adrenergic non-selective blockers, phentolamine and propranolol in concentrations of (10-8 and 10-5 M) were used to elucidate the exact mechanism mediating the relaxant effect of the ethanolic extract of Fagonia cretica linn. Results revealed that Fagonia cretica exhibited a dose-dependent relaxant activity on rabbit intestine similar to that produced by standard adrenaline with, Emax= [56.4 ± 7.5], [7.2 ± 4.3] and EC50= [0.12 ± 0.27], [9.85 ± 1.6] x 10-6 respectively. This effect was mediated through both ? and ? adrenoceptors, whilst there is no participation of direct muscle relaxant in mediating the relaxant effect of the plant extract. More detailed studies were recommended to deeply investigate and confirm these findings by using other techniques.